Immunohistochemical expression of BCL-2 in colorectal cancer and its association with clinicopathological parameters: a cross-sectional study from an Indian tertiary care center - Bhargavi, Alluri Hema; H. M., Sudha; Manasa, M. S. (International Journal of Research in Medical Sciences, 2025)
Background: Colorectal cancer (CRC) is among the leading causes of global cancer mortality and is steadily increasing in India. Despite advances in multimodal therapy, treatment resistance and recurrence remain major challenges. BCl-2, an anti-apoptotic protein, has emerged as a potential biomarker of tumor aggressiveness and therapeutic response. Objectives were to evaluate BCl-2 immunoexpression in CRC tissues and correlate expression levels with key clinicopathological features. Methods: A cross-sectional observational study was conducted on 60 histopathologically confirmed CRC cases. Formalin-fixed paraffin-embedded samples were stained using standard immunohistochemistry protocols. BCl-2 expression was scored based on percentage of positively stained tumor cells. Clinical data and pathological variables, including tumor location, histological subtype, grade, stage, and lymph node involvement, were recorded. Statistical significance was evaluated using chi-square/Fisher’s exact test (p<0.05). Results: BCl-2 positivity was identified in 96.7% of CRC cases, with 46.7% demonstrating strong cytoplasmic staining. A significant association was observed between BCl-2 expression and tumor location (rectum) as well as histological subtype (adenocarcinoma NOS). Although higher BCl-2 expression was noted in moderately differentiated tumors, this relationship did not reach statistical significance. No significant associations were found with tumor grade, stage, lymph node status, age, or sex. Conclusions: BCl-2 is frequently expressed in colorectal carcinoma, indicating its role in tumor survival; however, its limited correlation with clinicopathological parameters suggests it is not an independent prognostic marker. Further studies integrating additional apoptotic and molecular markers are needed to clarify its prognostic and therapeutic value.